ENT600 : Nicosub / Syahirah Ismail … [et al.] - Ismail, Syahirah; Zakaria, Muhammad Khairi; Hassan, Nor Hafifah; Ab Ghani, Nadzatul Shima; Ampri, Khairul Azreen (2015)
• Nicosub is an electronic equipment which have similar component with vape and e-cigarette • It use herbal remedies as a replacement of nicotine and simple technologyto improvise the traditional method of using herbal. • The scent that comes from cinnamon oil will trigger the user to overcome the addiction of nicotine. This is because herbal remedies itself have mental affect properties that can alter the urge sensation to smoking • The design of this device that resembles a cigarette is to change the minds of consumers as real because there are a lot of lip service sense of touch which is also a problem of addiction for smokers who want to bite their lip.